The linguistic and construct validity of the Malay version of the Coping Self-Efficacy Scale (CSES-My): Evidence from a sample of Malaysian parents of children with leukemia or lymphoma - Chai-Eng Tan; Kit-Aun Tan; Sie Chong Doris Lau; Kok Hoi Teh; Sherina Mohd Sidik (Belitung Nursing Journal, 2024)
Background: Parents of children with hematological cancers such as leukemia and lymphoma need to cope with stress related to their child’s diagnosis. The Coping Self-Efficacy Scale is a widely used and validated tool to measure an individual’s confidence in dealing with stressful situations. Appropriate translation and validation are needed to produce a localized language version suitable for Malaysian contexts.